PRESTASI PENGEMUDI TRUK ANGKUTAN KAYU DARI BERBAGAI KELOMPOK UMUR (Logging truck drivers' performances at several-age groups) - Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1990)
An  invelfigation on  logging truck  drivers' performances was conducted  in West Kali1t14ntan Province in 1988. Tfae objective of tile investigation iB to find out the logging truck drivers' performances at several Olle lt1'0UPB.flae  driven  of  Niaan  TZ 50 logging trucks at a logging company were observed using time study.  To Achieve the lfudy' objective, tile driven were categorized into '(ourgroups based on their age, namely <; 30, > 30-36,  > 36-40, and > 40 year& The result  of tile study  w.,re as follow:1. Logging truck driversat the loggingcompany are relatively old with the age between 30 and 45 years.2. Loging  truck driversperformances with" the age groups of~   30, > 30-36,  > 35-40,  and> 40 years were 102.81 m3-km/hour, 796.80 m3-km/hour, 745.07 m3-km/hour and 684.54 m3-km/hour, respectively.